The kinematics of taekwon-do back kick - Wasik, J.; Gora, T. (Baltic Journal of Health and Physical Activity, 2016)
Background: The back kick (in taekwon-do terminology referred to as dwit chagi) is considered a powerful weapon in taekwon-do sparring. This paper attempts to identify the kinematic factors affecting the efficiency of the back kick on the basis of values obtained for foot and knee velocities and the duration of the kick.